IMPROVING SPEAKING ACTIVE ABILITY BY USING DIRECT METHOD ON 2ND SEMESTER OF MIDWIFERY STUDENTS OF STIK BINA HUSADA PALEMBANG - Arief Pamuji (Jurnal Didascein Bahasa, 2018)
The objective of this research was to find out whether or not thereis an improving speaking active ability by using direct method on 2nd semester of midwifery students of STIK Bina Husada Palembang. This research was true experimental design the sample of this research was taken by using total sampling with total 70 students of midwifery students at STIK Bina Husada Palembang. The data were obtained by using speaking test on pre and post. To verify the hypotheses, the primary data were analyzed by using t-test and paired sample corellation analyses by SPPSS version 22 computer Program Based on the data analysis, the improving speaking active ability by using direct method Based on the data analysis, t test in the pre test and post test experiment was pre 68 and post 81 and the paired sample correlation got 0.770 at the significance level of p <0.05. Because the t and r-obtained values were higher.And from the average score obtained by students it can be seen that there was significant improving speak active ability especially in comprehension and fluency. It can be concluded that, the direct method usage in the class can improve the students’ speaking active ability Keywords: direct method, and speaking.